Carbonization Kinetics of Various Biomass Sources - Didem Özcimen; Ayşegül Ersoy-Mericboyu (Journal of Chemical Engineering Research Updates, 2014)
Hazelnut shell, apricot stone, grapeseed and chestnut shell samples were carbonized in a thermogravimetric (TG) analyzer at different conditions to determine the carbonization kinetic parameters. Three different calculation methods and 22 different model equations concerning solid-state rate controlling mechanisms were used for the kinetic analysis of the carbonization TG curves. A computer program in BASIC which enables regression analysis, was used to calculate the kinetic parameters from experimental TG data. It was observed that the different values of Arrhenius parameters (E and Log A) were obtained depending on the method of calculation, the gaseous atmosphere and the sample properties. The most appropriate kinetic model which represents the carbonization of the cellulosic and lignin ingredients of the biomass samples were found as f(α)=(1−α)2 and f(α)=0.5·(1−α)·[−ln(1−α)]−1, respectively.